Ageism and Discourses of Older People on Old Age and Aging in Chile - Pavez-Lizarraga, A; Pallavicini-Magnere, P; Baeza-Correa, C; Faure-Bascur, E (UNIV AUTONOMA BARCELONA, 2023)
The results that we present, account for the meanings associated with discourses of Chilean older people, about old age and aging. As a frame of reference, we draw on critical gerontology and feminist and intersectional approaches to the conditions of aging in Latin America. We work from the biographical method. The reiteration of negative stereotypes in relation to the "old subject" was verified, considering illness, loss and precariousness as predominant characteristics. Similarly, we observe tensions in the identification processes associated with old age, distancing themselves from the negative stereotypes associated with this stage. We verified continuity and changes in the gender role. We present speeches that emphasize self-care and social participation with age peers, as an emergency against negative stereotypes. The influence of ageism in discourses is concluded, reinforcing the devaluation of this stage for those who live it.